2010
DOI: 10.3102/0013189x10370781
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Effect of Education in an Information Technology–Penetrating Economy

Abstract: This article examines the economic effect of education in terms of its impact on the earnings of workers in an information technology (IT)-diffusing economy, based on data from Hong Kong's 2006 bycensus and survey on the usage and penetration of IT in industries. Education enhances the productivity of workers and increases their lifetime incomes. However, technological advances, if deskilling, may exert an adverse effect on workers' earnings. The analysis of the economic effect of education is complicated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A study by Chan (2010) showed that the diffusion of information technologies in workplaces exerts a negative earnings effect, but has a positive interaction effect on earnings between educational attainment and the level of IT diffusion in the industries in which workers are involved. In order to counter the negative effects of the increasing diffusion of information technology on workers' earnings, the Hong Kong workforce needs to receive more education; and, in this context, the Hong Kong Government's decision to expand the provision of post-secondary education to allow more young people to go beyond secondary level was justified.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…A study by Chan (2010) showed that the diffusion of information technologies in workplaces exerts a negative earnings effect, but has a positive interaction effect on earnings between educational attainment and the level of IT diffusion in the industries in which workers are involved. In order to counter the negative effects of the increasing diffusion of information technology on workers' earnings, the Hong Kong workforce needs to receive more education; and, in this context, the Hong Kong Government's decision to expand the provision of post-secondary education to allow more young people to go beyond secondary level was justified.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%